ANALISIS PANDANGAN POLITIK THOMAS AQUINAS - Simplesius Sandur (STIKAS Santo Yohanes Salib Kalimantan Barat, 2019)
Thomas Aquinas bases his political theory on the Aristotelian philosophy. Man is zoon politicon says Aristotle in his famous work the Politics. Politics in Thomas’ approach has a glorious purpose that is to create bonum commune. To realize this political program, the Angelic Doctor proposes not only politics in true sense but also ethics. Politics presupposes ethics. In modern society, maybe it would be meaningless if we perceive political reality which makes deep separation and distinction between politics and ethics. The result of this separation, in fact, is a disharmony of society. The disharmony of society in our analysis based on Thomistic political philosophy, derives from an absolut freedom in which man is understood in his ‘nature’ as an autonomistic person.